Análisis de la gestión de riesgos de desastres en espacios turísticos, estudio de caso: Quinta Juan León Mera, parroquia Atocha – Ficoa, Ambato. - Bedón Naranjo, Priscila Valeria (2022)
The objective of this case study was to analyze the management of disaster risks in tourist areas, the case of Quinta de Juan León Mera, Atocha - Ficoa parish, Ambato, using the qualitative and quantitative methodology that allows analyzing and evaluating the risks of both tourists as of the Quinta Juan León Mera from an inspection of the open spaces and the closed spaces that the villa has, in addition to the collaboration of the administrator of the Quinta Juan León Mera in providing information to be able to carry out the collection of information from the part structural, non-structural, social and functional, which allows knowing what risks the Quinta Juan León Mera is exposed to and how to act before, during and after an emergency or disaster, providing information on the percentage of visitors from July to December 2021 and know the percentage of people who come to the place and be prepared for a risk event, both n Both natural and anthropic that may exist within the Quinta de Juan León Mera each indicator that makes up each aspect evaluated for decision-making in carrying out priority actions and knowing what percentage it contributes to the performance and risk reduction of the quinta that Based on its analysis, it was determined that the fifth Juan León Mera is exposed to seismic risk, structural and environmental fires, after the analysis of information, the results can be socialized with the authorities to carry out appropriate measures. Finally, it is important to mention the importance of the evaluation based on diagnostic instruments that allow visitors to know the reality of the facilities of this tourist space and subsequently carry out the risk reduction plan. Keywords: Risk, Reduction, Anthropic, Disasters, Emergency, Disasters.